EXPLORING THE SIGNIFICANT FACTORS IN ENGAGING SOLAR ENERGY APPLICATION FOR CHILDREN HOME IN PERAK: A CASE STUDY OF SULTAN ABDUL AZIZ CHILDREN HOME IN KUALA KANGSAR, PERAK - Nur Sahida Abdul Rahman,; Nur Azfahani Ahmad, (Journal of Islamic, Social, Economics and Development, 2021)
People in Malaysia is unaware of the situation that electricity fossil-based resourcesmay be depleted in the future due to its rapid consumption. From rapid development inMalaysia, it is shown that Malaysia will continues to consume a large amount of electricity inthe near future that will decrease the resources of fossil fuel. At the moment, Malaysian arelack on information and knowledge regarding the essential of renewable energy that canrepresent as a supplement power for electricity. Frequent blackouts can also occur in the futureif the non-renewable resources deplete. It also can happen to many charity homes in Malaysiathat used the main power supply for their electricity. Most charity homes in Malaysia areresponsible to acts as a shelter for children in Malaysia which depended on supplied electricityfrom the main utility, which may face power blackouts from time to time. Therefore, it isnecessary to find a solution to overcome this situation by using renewable energy. The mostaccessible renewable energy that can be gained in Malaysia is solar energy. Therefore, it iswise to propose sustainable energy consumption for Children's Home in Malaysia which isbased on the application of solar energy. The aim of this research is to explore theestablishment of solar energy applications as supplement energy for electricity for children'shomes in Perak, Malaysia. The focus of this study is to encourage people in Malaysia, especiallyat the level of non-government organisation (NGO) to cultivate awareness of energy and to useenergy generated from solar energy in the near future.